Increased cancer rates in patients with chronic hepatitis C. (22nd December 2019) - Nyberg, Anders H.; Sadikova, Ekaterina; Cheetham, Craig; Chiang, Kevin M.; Shi, Jiaxiao X.; Caparosa, Susan; Younossi, Zobair M.; Nyberg, Lisa M.
Abstract: Aims: As previous reports show an association of chronic hepatitis C (HCV) with hepatocellular carcinoma (HCC) and non‐liver cancers, we examine the association of HCV with liver cancer and non‐liver cancers. Methods: Retrospective cross‐sectional study at Kaiser Permanente Southern California (KPSC) evaluating HCV and non‐HCV patients from 1 January 2008 to 12 December 2012. Cancer diagnoses were obtained from the KPSC‐SEER‐affiliated registry. Logistic regression analyses were used for rate ratios and time‐to‐event analyses were performed using Cox proportional hazards models, adjusted for age, gender, race, smoking and cirrhosis. Cancer rate ratios were stratified by tobacco, alcohol abuse, diabetes and body mass index (BMI). Results: The initial population and final population of multivariable analysis were N = 5 332 903 and N = 2 080 335 respectively. Cancer burden (all sites) was significantly higher in HCV than in non‐HCV patients and HCV patients had a high rate of liver cancer. When liver cancer was excluded, cancer rates remained significantly increased in HCV. Unadjusted cancer rates were significantly higher in HCV compared to non‐HCV for oesophageal, stomach, colorectal, pancreas, myeloma, non‐Hodgkin's lymphoma, head/neck, lung, renal and prostate cancer. After stratification for alcohol abuse, tobacco, diabetes and BMI, increased cancer rates remained significant for all cancer sites, liver cancer and non‐Hodgkin's lymphoma. Multivariable analyses demonstrated a strong correlation between cirrhosis and cancer. Tobacco use and diabetes were also associated with cancer. In the absence of cirrhosis, HCV, tobacco use and diabetes significantly increased the cancer risk. Mediation analyses showed that cirrhosis was responsible for a large proportion on the effect of HCV on cancer risk. Conclusion: This study supports the concept of HCV as a systemic illness and treating HCV regardless of disease severity and prior to progression to cirrhosis.